Solution nitriding of AISI 430 ferritic stainless steel - Hussain, P (2009)
This paper reports the work on solution nitriding of AISI 430 ferritic stainless steel. To study the phase transformation at the steel, calculation using Thermocalc software was carried out. Metallographic study, XRD examination and assessment of the samples’ hardness after the treatment was performed to examine the result of the treatment. The microstructure of the nitrided samples contains martensite and coarse ferrite. The martensite development is begun at the outer layer and grows further to the core when nitriding time is increased. A partial martensite formation is also taken place at the core which is initiated at the ferrite’s grain boundary. The existence of the martensite structure contributes to the hardness improvement of the steel. However, nitrogen diffusion is also believed to increase the hardness of the martensite. Prolonging the nitriding time diffuses more nitrogen into the material. It stimulates more martensite as well as the hardness improvement. Nitriding for four hours brings to a fully martensitic transformation and hardens the entire cross section of the sample.